2022
DOI: 10.3390/math10142374
|View full text |Cite
|
Sign up to set email alerts
|

Functional Data Analysis for the Detection of Outliers and Study of the Effects of the COVID-19 Pandemic on Air Quality: A Case Study in Gijón, Spain

Abstract: Air pollution, especially at the ground level, poses a high risk for human health as it can have serious negative effects on the population of certain areas. The high variability of this type of data, which are affected by weather conditions and human activities, makes it difficult for conventional methods to precisely detect anomalous values or outliers. In this paper, classical analysis, statistical process control, and functional data analysis are compared for this purpose. The results obtained motivate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Given the available data, variation in pollutant levels during the restrictions were calculated by first determining the mean values for the whole sampling period, and secondly comparing these with the corresponding period in 2019. Rigueira et al (2022) studied PM10 variation during COVID-19 restrictions comparing with data collected from 2015 in a station located in the western area of Gijón. They concluded that reductions observed in PM10 concentration during the lockdown were nothing extraordinary.…”
Section: Resultsmentioning
confidence: 99%
“…Given the available data, variation in pollutant levels during the restrictions were calculated by first determining the mean values for the whole sampling period, and secondly comparing these with the corresponding period in 2019. Rigueira et al (2022) studied PM10 variation during COVID-19 restrictions comparing with data collected from 2015 in a station located in the western area of Gijón. They concluded that reductions observed in PM10 concentration during the lockdown were nothing extraordinary.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the concept of depth makes it possible to work with observations, defined in a given time interval, in the form of curves, instead of having to summarize the information contained in these curves into a single value, such as the mean [25]. In this case, the Modified Band Depth (MBD) [45] has been selected as it has demonstrated a better performance in the analysis of environmental data with this approach [46]. Functional directional outlyingness is considered to increase the accuracy in the detection of outliers.…”
Section: Functional Data Analysismentioning
confidence: 99%
“…The study demonstrated the effectiveness of functional data analysis in detecting patterns and outliers in nitrogen dioxide concentrations, highlighting the limits of traditional approaches as well as the advantages of functional data analysis for comprehensive air pollution control. Rigueira et al [5] studied the application of functional data analysis for detecting outliers and evaluating the impact of the COVID-19 outbreak on air quality in Gijón, Spain in 2022. The study compared the methodology of classical analysis, statistical process control, and functional data analysis, revealing that functional data analysis outperformed the other two methods in spotting outliers in high-variability data.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Like in Wang et al [8] study, we also used data smoothing technique (and used Fourier basis as it was done by Torres et al [2]) and tested the significance of difference among different regions using ANOVA. We also performed outliers detection as similar outliers' analysis were performed by Torres et al [2] and by Rigueira et al [5].…”
Section: Literature Reviewmentioning
confidence: 99%